2016
DOI: 10.1111/1744-7917.12348
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of memory retention in a parasitic wasp: an effect of host manipulation by Wolbachia?

Abstract: Several factors, such as cold exposure, aging, the number of experiences and viral infection, have been shown to affect learning ability in different organisms. Wolbachia has been found worldwide as an arthropod parasite/mutualist symbiont in a wide range of species, including insects. Differing effects have been identified on physiology and behavior by Wolbachia. However, the effect of Wolbachia infection on the learning ability of their host had never previously been studied. The current study carried out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…To avoid superparasitism, females can detect and discriminate host quality before depositing eggs and can label the host with host marking pheromone (HMP) after oviposition 21,36 . However, infected females show a lower host discrimination ability 11,23,37 . Because they may be unable to recognise host eggs parasitised by other wasps, they are more likely to lay their own egg clutches, resulting in superparasitism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid superparasitism, females can detect and discriminate host quality before depositing eggs and can label the host with host marking pheromone (HMP) after oviposition 21,36 . However, infected females show a lower host discrimination ability 11,23,37 . Because they may be unable to recognise host eggs parasitised by other wasps, they are more likely to lay their own egg clutches, resulting in superparasitism.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that females showed a lower rate of superparasitism with lower Wolbachia titres induced at high temperature, possibly due to Wolbachia inducing memory loss in infected females. Infected wasps often show reduced memory duration, and may “forget” information on host quality or previously parasitised eggs 37 . This hypothesis is supported by studies showing that Wolbachia can invade the brain and replicate rapidly in the central nervous system of its host 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reveal Wolbachia mediates the expression of dopamine related genes, and decreases the sleep quality of their insect hosts (Bi et al, 2018). Kishani Farahani et al revealed that Wolbachia-infected wasps display shorter memory retention in new environments compared with uninfected wasps; in this way, they can increase the broadcast of Wolbachia by forgetting the trace connected with previous environments (Kishani Farahani et al, 2017) It was reported that wVulC Wolbachia-infected Armadillidium vulgare, a terrestrial isopod, had worse ability to learn and memorize the correct direction after training compared to a Wolbachia-free group. Wolbachia infection in A.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis based on ITS-2 gene apparently supported that our two strains are part of the highly homogeneous T. dendrolimi genetic pool and can be assumed to have similar genetic backgrounds, as suggested by Kishani et al . 44,70 . Such relationship was further substantiated by similar COI-based reconstruction and by undifferentiated COI and Cytb sequences between two strains.…”
Section: Discussionmentioning
confidence: 99%